Association between values of anthropometric indicators, Total Antioxidant Capacity and Malondialdehyde in adults: a population-based study - thamires ribeiro haves; LIMA, Raquel; RIBEIRO, Marina; Boico, Vitor; FERREIRA, Flavia; GONÇALVES, María da Conceiçao; ALMEIDA, Alessioo; MORAES, Ronei; SILVA, Alexandre; Cardoso, Glêbia; TEIXDEIRA DE LIMA, Roberto; COSTA, María José; et al. (Nutrición Clínica y Dietética Hospitalaria, 2021)
Background: Research regarding the correlation between obesity and oxidative stress is important due to the health complications they entail, and elucidating this association through the waist-to-height ratio is of great interest because it is an important anthropometric indicator of cardiovascular and metabolic diseases’ risk associated with obesity. The aim of this study was to gain a better understanding of the association between waist-to-height ratio and total antioxidant capacity and malondialdehyde values in adults. Methods: A cross-sectional population-based study was conducted in 265 individuals from a municipality in northeastern Brazil. Epidemiological data were collected, and anthropometric and biochemical evaluations were performed. Multiple regression analysis using the median of the variables was applied. Results: In the total sample, more than half of the participants were overweight or obese. The mean value of 0.54cm waist-to-height ratio, with the majority of adults (65.28%) presenting with slight elevation waist-to-height ratio. A correlation was found between waist-to-height ratio and BMI with the values of total antioxidant capacity (t= -2.96; p=0.003) and malondialdehyde (t=2.87, p=0.004), as well as LDL (t=3.19, p=0.002), triglycerides (t=3.17; p=0.002). Conclusion: Abdominal obesity, reflected by a slight elevation in the waist-to-height ratio, corroborated by BMI was indicated as an aggravating factor in oxidative stress increase because it was positively related with malondialdehyde values and negatively with total antioxidant capacity values in this adult population.